Trypan blue removal from water with zein sorbents and laccase - Marshall, Tatianna (SN Appl Sci, 2021)
ABSTRACT: Zein-based materials were used to remove Trypan blue from water under flow conditions and in batch tests. In flow tests, zein dissolved at pH = 13 was injected in sand columns and subsequently coagulated with CaCl(2), to create an adsorbent filter which removed over 99% of Trypan blue. Batch tests were conducted using zein powder, zein dissolved at pH = 13 and coagulated with CaCl(2), Fe(2)Cl(3) or citric acid, and zein dissolved in ethanol and then coagulated with water. The highest Trypan blue removal was achieved with zein powder (4000 mg Trypan blue/kg sorbent, as determined through spectrophotometry), followed by zein coagulated with Fe(2)Cl(3) (500 mg Trypan blue/kg sorbent) and with other salts (140 mg Trypan blue/kg sorbent). Differences in the sorption efficiency are attributed to differences in the surface area. The sorption isotherm of Trypan blue onto zein-based sorbents was a Type II isotherm, suggesting physisorption. Desorption of Trypan blue was limited when zein-based coagulated sorbents were immersed in pure water. Trypan blue could be degraded by free laccase in water, as determined through spectrophotometry and electrospray ionization mass spectroscopy (ESI-MS). Trypan blue could also be degraded by laccase when zein-based laccase-containing sorbents were prepared at pH = 10, using Fe(2)Cl(3) as coagulant. GRAPHIC ABSTRACT: [Image: see text] SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s42452-020-04107-w.